2018
DOI: 10.3389/fnut.2018.00036
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and Ionomics of Potato Tuber Reveals an Influence of Cultivar and Market Class on Human Nutrients and Bioactive Compounds

Abstract: Potato (Solanum tuberosum L.) is an important global food crop that contains phytochemicals with demonstrated effects on human health. Understanding sources of chemical variation of potato tuber can inform breeding for improved health attributes of the cooked food. Here, a comprehensive metabolomics (UPLC- and GC-MS) and ionomics (ICP-MS) analysis of raw and cooked potato tuber was performed on 60 unique potato genotypes that span 5 market classes including russet, red, yellow, chip, and specialty potatoes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 116 publications
(120 reference statements)
2
39
1
1
Order By: Relevance
“…However, the reason for these strong 334 correlations remains unclear as no direct link has been reported so far and further investigation 335 is needed. Metabolite correlations of potato groups differing in the genetic background have 336 been previously reported (Dobson et al, 2010;Chaparro et al, 2018). Significant metabolite 337 variation and metabolite-metabolite correlations were detected from a collection of 60 unique 338 potato genotypes that span 5 different market classes such as russet, red, yellow, chip, and 339 speciality (Chaparro et al, 2018), where authors concluded that metabolite diversity and 340 correlations data can support the potential to breed new cultivars for improved health traits.…”
Section: Metabolic Correlation Network Analysis 305mentioning
confidence: 92%
See 1 more Smart Citation
“…However, the reason for these strong 334 correlations remains unclear as no direct link has been reported so far and further investigation 335 is needed. Metabolite correlations of potato groups differing in the genetic background have 336 been previously reported (Dobson et al, 2010;Chaparro et al, 2018). Significant metabolite 337 variation and metabolite-metabolite correlations were detected from a collection of 60 unique 338 potato genotypes that span 5 different market classes such as russet, red, yellow, chip, and 339 speciality (Chaparro et al, 2018), where authors concluded that metabolite diversity and 340 correlations data can support the potential to breed new cultivars for improved health traits.…”
Section: Metabolic Correlation Network Analysis 305mentioning
confidence: 92%
“…For example, metabolic profiles in different life cycle stages of potato 253 tubers were characterized to link temporal changes in metabolites related to trait development 254 . In a recent study, comprehensive metabolomics and ionomics analysis on 255 raw and cooked potato tubers of 60 unique genotypes were performed to understand the chemical 256 variation and nutritional values in different varieties (Chaparro et al, 2018). In another study, 257 storage of commercial cultivars at 20-22 C in the dark suggested a significant decrease in sucrose 258 and fructose (Uri et al, 2014).…”
Section: Statistical Analysis 159mentioning
confidence: 99%
“…Furthermore, the formation of doubly charged species was limited by ensuring that Ce ++ :Ce + ratio was below 0.03. A calibration curve was created by evaluating 7 dilutions of a Peach metabolic priming under carbon sufficiency/starvation 7 multi-element stock solution, created by a mixture of single element stock standards (Inorganic Ventures, Christiansburg, VA, USA) (Chaparro et al, 2018). Calibration curve was matrix matched to the samples, 2.5% HNO 3 and ppb In.…”
Section: Fruit Quality Analysesmentioning
confidence: 99%
“…Metabolomic studies have been crucial in potato breeding mainly because tuber quality traits such as content and quality of starch, chipping quality, flesh color, taste, and glycoalkaloid content, etc., have been shown to be linked to a wide range of metabolites and alteration in metabolic networks [14][15][16] . Metabolic profiles in different life cycle stages of potato tubers were characterized to link temporal changes in metabolites to their acrylamide-forming potential 17 .…”
mentioning
confidence: 99%
“…Metabolic profiles in different life cycle stages of potato tubers were characterized to link temporal changes in metabolites to their acrylamide-forming potential 17 . In a recent study, comprehensive metabolomics and ionomics analysis on raw and cooked potato tubers of 60 unique genotypes spanning five marker classes were performed to understand the chemical variation and nutritional values in different varieties 15 . Such studies presented the metabolite diversity, which laid the foundation to generate potato cultivars with enhanced nutritional and processing qualities for human health.…”
mentioning
confidence: 99%